Construction of space identity: Socio-historical and political dialectics in the globalisation era - Siti Aminah (Faculty of Social and Political Science, Universitas Airlangga, 2018)
Every local government in Indonesia seeks to construct a space/place identity. Competition between identities becomes a key element in relation to recognition, diﬀerentiation, and commodification in the context of decentralisation’s implementation. This article has studied Mojokerto’s identity development as a part of the territorial administration system with regional autonomy. Policymakers designated Mojokerto as the host of Mojopahit House’s identity. The geographical space of Mojokerto competes in terms of identity, which underwent another comparison and intense competition with other regions’ identities. Why was Mojopahit House determined as the identity of Mojokerto by the government at the national, provincial, and municipal levels? Based on such a question, this paper employed the politico-spatial approach using the qualitative analysis method and interpretive approach. This study found that the policymakers viewed Mojopahit House as the most suitable symbol in the identity competition between regions and autonomous regions. It can be turned into a fundamental icon to project political value, economic value, and/or the place attributes. Mojopahit House has becomes a representative of the local-traditional, global, and political economy identity. To conclude, the development of space identity lies within heritage conservation policy and globalisation pressure.